Transformasi Diri: Membangun Keseimbangan Mental dan Spiritual Melalui Proses Islah - Mustaqim, Dede Al (Jurnal Kawakib, 2023)
The balance between mental well-being and spiritual life has an important role in achieving better personal development. The process of Islah in Islam was introduced as a means to achieve this balance. The purpose of this research is to find out how to build mental and spiritual balance through the process of reconciliation. The research method used is library research, which involves analysis and synthesis of the relevant literature as a data source. The result of this study is that the Islah process is important in self-transformation. The stages in Islah include self-awareness, reflection and introspection, eliminating vices, increasing goodness, and developing a relationship with God. Through self-transformation through the process of Islah, a strong mental and spiritual balance can be built, happiness in life can be achieved, good relationships with oneself and others can be improved, and positive contributions to society can be made.